2010
DOI: 10.1016/j.jbiomech.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Cells in 3D matrices under interstitial flow: Effects of extracellular matrix alignment on cell shear stress and drag forces

Abstract: a b s t r a c tInterstitial flow is an important regulator of various cell behaviors both in vitro and in vivo, yet the forces that fluid flow imposes on cells embedded in a 3D extracellular matrix (ECM), and the effects of matrix architecture on those forces, are not well understood. Here, we demonstrate how fiber alignment can affect the shear and pressure forces on the cell and ECM. Using computational fluid dynamics simulations, we show that while the solutions of the Brinkman equation accurately estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 50 publications
2
73
0
Order By: Relevance
“…Flow-induced stresses on a cell are a function of flow rate and, in contrast to an autocrine or paracrine signaling stimulus, independent of cell density. Shear stress has long been known to play a role in EC migration (3,(33)(34)(35)(36); however, in our system, cells are suspended in a 3D matrix, and the presence of this porous medium causes the force due to fluid pressure gradient across the cell to dominate the fluid shear force (37). By modeling a cell as a sphere embedded in a porous medium, we found the force due to the pressure drop across the cell (F pm ) relative to the shear stress imparted by the fluid (F s ) scales as…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow-induced stresses on a cell are a function of flow rate and, in contrast to an autocrine or paracrine signaling stimulus, independent of cell density. Shear stress has long been known to play a role in EC migration (3,(33)(34)(35)(36); however, in our system, cells are suspended in a 3D matrix, and the presence of this porous medium causes the force due to fluid pressure gradient across the cell to dominate the fluid shear force (37). By modeling a cell as a sphere embedded in a porous medium, we found the force due to the pressure drop across the cell (F pm ) relative to the shear stress imparted by the fluid (F s ) scales as…”
Section: Discussionmentioning
confidence: 99%
“…Pressure forces from flow past a cell in a 3D matrix lead to a transcellular stress gradient (37), and this stress results in asymmetric force in cell-matrix interactions-e.g., tensile force on the upstream side and compressive force on the downstream side. Previous work demonstrates that FAK colocalizes with activated integrins and activates Src kinase (28,29), which modulates traction forces important for tumor cell migration (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Fluid flow is known to enhance matrix synthesis within TE constructs during perfusion culture. 19,40,50 Furthermore, differences in fibrillar collagen organization of the ECM, which are flow dependent, 51 could also explain the ECM differences that were observed by PTA staining as the ECM morphology could influence the binding mechanism of PTA to the ECM proteins. In Figure 5, it may also be observed that the difference in collagen content, as determined by Picrosirius Red staining, for the different flow rates is less pronounced than the one observed with the PTA staining.…”
Section: Papantoniou Et Almentioning
confidence: 99%
“…This elevated fluid pressure drives interstitial flow (IF) and alters chemical transport within the tumor (13), and IF influences tumor cell migration through the generation of autocrine chemokine gradients (14). Equally important, although not as well understood, is the physical drag imparted on the ECM and constitutive cells (15) by IF, which is analogous to the FA-activating shear stresses generated on endothelial cells by hemodynamic forces (16). With endothelial cells, shear stress can be the dominant mechanical stimulus that induces FAK activation and cytoskeletal remodeling; however, for cells embedded within a porous matrix scaffold, the ratio of the force due to the pressure drop across the cell to the total shear force is inversely proportional to hydrogel permeability (SI Appendix, Eq.…”
mentioning
confidence: 99%